the effect PENGARUH PENGGANTIAN KONSENTRAT MENGGUNAKAN AMPAS TEMPE DAN SUPLEMENTASI COMPLETE RUMEN MODIFIER (CRM) TERHADAP KONSUMSI DAN KECERNAAN PROTEIN KASAR PAKAN DOMBA - Hutasoit, Irma Uli; Suhartati, Fransisca Maria; Suryapratama, Wardhana (ANGON: Journal of Animal Science and Technology, 2024)
The study aims to examine the effect of concentrate replacement using tempeh dregs and Complete Rumen Modifier (CRM) supplementation on the consumption and digestibility of crude protein in sheep feed. The study used 18 local male sheep aged 7-8 months with an average weight of 20±2.34 kg. This study used a Randomized Group (RAK) design and used a type of experimental research, as a group as well as a repeat of the initial body weight of sheep after the adaptation period as many as 6 groups and 3 treatments, including P1: Ammoniated rice straw ad libitum + concentrate 2.5% DM of body weight (control), P2: Ammoniated rice straw ad libitum + tempeh dregs 2.5% DM of body weight, and P3: Ammoniated rice straw ad libitum + tempeh dregs 2.5% DM of body weight + 1% CRM. The variables observed in the study were consumption and digestibility of crude protein. Based on the results of the analysis of treatment variance, the effect was very real (P<0.01) on crude protein consumption with an average consumption of P1, P2, P3 treatments, respectively 10.26±0.05; 14.35±0.78; 14.02±0.88 (g/head/d) and a significant effect (P<0.005) on digestibility with crude protein digestibility rate of P1, P2, P3 treatment respectively at 59.44±3.65%; 67.85±3.44%; 63.56±4.83%. Based on orthogonal contrast tests, tempeh dregs can replace concentrate feed entirely and even increase crude protein consumption and digestibility by 3.90% and 3.93% respectively without 1% CRM supplementation. Keywords: CRM, tempe dregs, lamb, crude protein, consumption, digestibility.